63. Mobile Learning in Developing Nations - Motlik, Scott (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2008)
This paper looks at the diffusion and applications of mobile phone technology in Asia and Africa, compared with North America. It indicates that Asian distance education can be the global leader in the development of educational uses for the mobile phone; and it considers the potential for mobile learning in Africa and other developing regions. The paper concludes that it would be a serious disservice to learners and instructors if Asia and Africa were to cast their lot with Web-based learning. By comparison, mobile phone technology is widespread, easy to use, and familiar to learners and instructors.